Influence of cabruca and full sun cultivation systems on the chemical quality of cocoa kernel (Theobroma cacao L.) from Southern Bahia: an integrated analysis of the metabolic profile and element transfer - Kobi, Hélia de Barros (Universidade Federal de Viçosa, 2024)
The search for chemically high-quality cacao is driven by the global demand for chocolate but is threatened by the accumulation of heavy metals. The objective of this thesis was to investigate the metabolic profile (fatty acids, phenolic compounds, and methylxanthines) and the transfer of chemical elements in beans, leaves, and soils of the cultivars CCN 51 and PS13.19, produced in cabruca and full sun systems in southern Bahia. In the first chapter, it was observed that the cultivation system influenced the fatty acid composition, with higher values of linoleic acid (3.21±0.05%) associated with the full sun system, although higher levels of total lipids (54.92±0.45%) were obtained in the cabruca system. The cultivation system also influenced PUFA composition, with higher values in the full sun system (3.21±0.05%). On the other hand, CCN 51 beans showed higher SFA content (61.74±0.50%) and a higher S/U ratio (1.62±0.03%). The PS13.19 cultivar exhibited higher levels of MUFA (36.71±0.34%) and UFA (39.62±0.82%). Lower levels of total phenolic compounds (193.33±50.18 mg GAE·100g1), total anthocyanins (52.35±21.67 mg AntT·100g1), and antioxidant properties (ABTS: 200.74±110.68 mol TE/g; DPPH: 249.39±82.12 mol TE/g) were found in the full sun system, especially in the PS13.19 cultivar. Higher levels of epicatechin (155,626.67±15,802.19 EIC) and catechin (23,625.57±15,802.19 EIC) were found in CCN 51 beans. In summary, genetic and management factors significantly influenced cacao chemical composition, indicating that the transition from cabruca to full sun may reduce total lipid and phenolic compound content. In the second chapter, the physicochemical characterization of the soil revealed the prevalence of acidic soils (pH 4.5 to 6.1), with deficiencies in fertility components (P, K, Ca2+, and Mg2+). Heavy metal levels in the soils were predominantly low; however, some areas showed Zn and Cr levels above the reference values established by COPAM (2011). Regarding the beans, no sample presented quantifiable levels of As, Pb, or Cd, and Cu levels (15.2 mg·kg1) were below the maximum tolerated limit (40 mg·kg1) established by Anvisa (2022). Additionally, the beans exhibited high levels of K (9.75±0.59 g·kg1) and P (5.23±0.37 g·kg1), and notable amounts of Fe (25.88±10.42 mg·kg1), Zn (50.92±7.23 mg·kg1), Cu (15.20±5.32 mg·kg1), and Mn (17.25±12.12 mg·kg1). A positive and consistent correlation was observed between Mn content in soil, beans, and leaves. The integrated PCA showed that the cabruca system is characterized by factors related to soil fertility, such as Ca2+, Mg2+, and SB. Therefore, the results provide evidence that cacao beans from southern Bahia do not present contamination by Cd, Pb, or As and possess high mineral richness; however, the insufficiency of essential nutrients and the potential environmental risk of soil Cr represent challenges for the sustainability of the crop. Keywords: cacao trees; CCN 51; PS 13.19; bioactive compounds; cocoa butter; antioxidant properties; primary metabolites; secondary metabolites; flavonoids; alkaloids; nutrients; minerals; heavy metals

A busca por cacau de qualidade química é impulsionada pela demanda global de chocolate, mas é ameaçada pelo acúmulo de metais pesados. O objetivo desta tese foi investigar o perfil metabólico (ácidos graxos, compostos fenólicos e metilxantinas) e a transferência de elementos químicos em amêndoas, folhas e solos, de cultivares CCN 51 e PS13.19, produzidas em sistemas cabruca e a pleno sol no Sul da Bahia. No capítulo um observou-se que o sistema de cultivo influenciou a composição de ácidos graxos, com maiores valores de ác. linoleico (3,21±0,05%) associados ao sistema pleno sol, embora maiores teores de lipídios totais (54,92±0,45%) tenham sido obtidos no sistema cabruca. O sistema de cultivo influenciou também a composição de PUFA, com valores mais elevados no sistema a pleno sol (3,21±0,05%). Por outro lado, amêndoas CCN 51 apresentaram maior teor de SFA (61,74±0,50%) e maior relação S/U (1,62±0,03%). A cultivar PS13.19 exibiu níveis mais elevados de MUFA (36,71±0,34%) e UFA (39,62±0,82%). Menores níveis de compostos fenólicos totais (193,33±50,18 mg GAE.100g1), antocianinas totais (52,35±21,67 mg AntT.100g1) e propriedades antioxidantes (ABTS: 200,74±110,68 mol TE/g e DPPH: 249,39±82,12 mol TE/g) foram encontrados no sistema pleno sol, especialmente na cultivar PS 13.19. Maiores níveis de epicatequina (155626,67±15802,19 EIC) e catequina (23625,57±15802,19 EIC) foram encontrados em amêndoas CCN 51. Em suma, os fatores genéticos e de manejo influenciaram significativamente a composição química do cacau, indicando que a transição de cabruca para o pleno sol pode reduzir o teor de lipídios totais e compostos fenólicos. No segundo capítulo a caracterização físico-química do solo revelou a prevalência de solos ácidos (pH de 4,5 a 6,1), com deficiências em componentes de fertilidade (P, K, Ca2+ e Mg2+). Os níveis de metais pesados nos solos foram predominantemente baixos; no entanto, algumas áreas apresentaram níveis de Zn e Cr acima dos valores de referência da COPAM (2011). Em relação às amêndoas, nenhuma amostra apresentou níveis quantificáveis de As, Pb e Cd, e os níveis de Cu (15,2 mg.kg1) estavam abaixo do limite máximo tolerado (40 mg.kg1) pela Anvisa (2022). Adicionalmente, as amêndoas apresentaram altos níveis de K (9,75±0,59 g.kg1) e P (5,23±0,37 g.kg1) e teores notáveis de Fe (25,88±10,42 mg.kg1), Zn (50,92±7,23 mg.kg1), Cu (15,20±5,32 mg.kg1) e Mn (17,25±12,12 mg.kg1). Observou-se correlação positiva e consistente entre o teor de Mn no solo, nas amêndoas e nas folhas. A PCA integrada demonstrou que o sistema cabruca é caracterizado por fatores relacionados à fertilidade do solo, como Ca2+, Mg2+ e SB. Portanto, os resultados fornecem evidências de que as amêndoas de cacau da região sul da Bahia não apresentam contaminação por Cd, Pb e As e possuem alta riqueza mineral; no entanto, a insuficiência de nutrientes essenciais e o potencial risco ambiental do Cr no solo representam desafios para a sustentabilidade da cultura. Palavras-chave: cacaueiros; CCN 51; PS 13.19; compostos bioativos; manteiga de cacau; propriedades antioxidantes; metabólitos primários; metabólitos secundários; flavonoides; alcaloides; nutrientes; minerais; metais pesados
Influência dos sistemas de cultivo cabruca e pleno sol na qualidade química de amêndoas de cacau (Theobroma cacao L.) do Sul da Bahia: uma análise integrada do perfil metabólico e da transferência de elementos
Keywords: Cacau - Efeito dos metais pesados - Análise; Cacau - Cultivo; Sistema cabruca; Compostos bioativos; Antioxidantes; Metabólitos; Flavonoides; Alcaloides; Nutrientes; Minerais; Metais pesados; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::QUIMICA, FISICA, FISICO-QUIMICA E BIOQUIMICA DOS ALIM. E DAS MAT.-PRIMAS ALIMENTARES